IDENTIFIKASI KETERAMPILAN GENERIK SAINS DALAM MODEL PEMBELAJARAN BERBASIS PROYEK - Juni Artini, Ni Putu; Budi Wijaya, I Komang Wisnu (Dharmas Education Journal (DE_Journal), 2023)
Generic science skills is important to be mastered so that students have good mastery of science concept, scientific attitudes and science process skills. In this independent curriculum era, learning including science is directed to use a project-based learning model. This study aims to identify the generic science skills contained in the project-based learning model. This research is classified as a literature study. The data sources for this research come from books, papers and other literature related to generic science skills and project-based learning models. The data analysis technique was carried out using content analysis techniques. The results of the study state that the project-based learning model can develop a variety of generic science skills, namely direct observation, indirect observation, logical framework, logical inference, mathematical modeling and causal relationships.